2017
DOI: 10.1177/0020872817742700
|View full text |Cite
|
Sign up to set email alerts
|

Voices of Ethiopian immigrant women

Abstract: This qualitative research article explored the lived experience of Ethiopian immigrant women in the Washington, DC, metropolitan area. Data were collected through face-to-face, semi-structured interviews with 14 participants. The themes that emerged included the important role family members who already lived in the United States played in connecting participants with housing, jobs, and educational opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Communication can be considered fundamental for a patient’s satisfaction and quality care. Several past studies identified that immigrants experienced poor quality care due to communication barriers and lack of skills of health care professionals to respond to different cultural needs (Adegboyega & Hatcher, 2017; Gerrish, Chau, Sobowale, & Birks, 2004; Jirwe, Gerrish, & Emami, 2010; Oliphant, 2017; Pang et al, 2003; Wiking, Johansson, & Sundquist, 2004). In the current mini study, participants felt that education, which they valued for themselves and their children, will have a positive effect on employment and consequently improve the health and well-being of families.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Communication can be considered fundamental for a patient’s satisfaction and quality care. Several past studies identified that immigrants experienced poor quality care due to communication barriers and lack of skills of health care professionals to respond to different cultural needs (Adegboyega & Hatcher, 2017; Gerrish, Chau, Sobowale, & Birks, 2004; Jirwe, Gerrish, & Emami, 2010; Oliphant, 2017; Pang et al, 2003; Wiking, Johansson, & Sundquist, 2004). In the current mini study, participants felt that education, which they valued for themselves and their children, will have a positive effect on employment and consequently improve the health and well-being of families.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data analysis, the researcher then abstracted five major themes and 14 care patterns. To conduct culturally competent research, free of stereotypes and discrimination, the researcher found that practicing reflexivity and cultural humility was beneficial throughout the research and data analysis processes (Aronowitz, Deener, Keene, Schnittker, & Tach, 2015; Oliphant, 2017; Yeager & Bauer-Wu, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this article, we examine how the researcher's own personal positions influence her qualitative study of 14 Ethiopian immigrant women in the United States (Oliphant, 2019). The researcher was a white, native-born U.S. citizen and doctoral student, from an upper middle-class background.…”
mentioning
confidence: 99%